Hexaminolevulinate blue light cystoscopy improves bladder cancer detection in comparison to white light cystoscopy: a prospective, comparative, within-patient controlled multicenter phase III bridging study in China - Hu, Hailong; Huang, Jian; Ma, Lulin; Zhang, Shudong; Guo, Jianming; Liu, Xiuheng; Guo, Yonglian; Wen, Jin; Zhang, Hongxian; Jiang, Shuai; He, Wang; Liu, Cheng; et al. (Frontiers in Urology, 2026)
Background and objectiveTo compare hexaminolevulinate (HAL) blue light cystoscopy (BLC) with white light cystoscopy (WLC) in the detection of bladder cancer.MethodsPatients received intravesical HAL (Hexvix®) and underwent WLC before randomization to undergo high-definition BLC (System blue). Lesions identified in either WLC or BLC were evaluated by a blinded panel. The primary efficacy endpoint was the proportion of patients with histology-confirmed tumors (Ta, T1, or CIS) and with at least one such tumor found by BLC but not by WLC. The secondary endpoints included the detection of CIS, lesion detection rates, false-positive rate, and safety.ResultsOf the 158 (160 screened patients) enrolled patients, 120 underwent WLC and were randomized (6 WLC, 114 BLC), and 97 were diagnosed with NMIBC. The mean age was 65.30 ± 12.18 years. Out of the 114 patients, 13 (11.4%) suffered from CIS; 84.6% (11/13) were detected with additional lesions by BLC; and 61.5% (8/13) were diagnosed solely by BLC. Compared with WLC, the proportion of patients with additional bladder cancer lesions detected by HAL BLC was 43.3% [(33.27%, 53.75%), p < 0.0001]. The proportion of patients with CIS lesions detected by HAL BLC and not by WLC was 9.6% (4.9%, 16.6%). The detection rates for CIS, Ta, T1, and T2–T4 tumors were 94.7%, 100%, 98.2%, and 100% for BLC and 42.1%, 76.1%, 91.2%, and 100% for WLC, respectively. The false-positive rates were 23.2% (19.2%, 27.7%) and 16.0% (11.9%, 20.8%) for BLC and WLC, respectively. A total of 95 patients (60.1%) reported 200 cases of AE, with 9 AEs being drug-related (fever, bladder pain, etc.). Nine device deficiencies (5.7%) occurred (eight quality issues and one device failure). No AEs and SAEs led to discontinuation.ConclusionsIn the setting of modern high-definition equipment, HAL BLC significantly improves the detection of bladder cancer with favorable safety.